NILAI-NILAI PENDIDIKAN BUDI PEKERTI DALAM NOVEL NEGERI PARA BEDEBAH KARYA TERE LIYE - Abdurrahman, Vivien Syofiana Diva, Harris Effendi Thahar, (Universitas Negeri Padang, 2017)
The purpose of this study is to descibe the character education in the novel Negeri Para Bedebah by Tere Liye. The data of this research is the aspect of the moral value of character found in the novel Negeri Para Bedebah by Tere Liye include the value of affection, hard work value, responsibility value, and sportive value. The data source of this research is novel Negeri Para Bedebah by Tere Liye. Data collcted by reading and understanding, inventorying, interpreting, classifiying, and summarizing data relating to values of character education in novel Negeri Para Bedebah by Tere Liye. Researh findings that is the value of charater eduation that is found in the novel of Negeri Para Bedebah by Tere Liye.Â Kata Kunci: nilai, pendidikan, budi pekerti, implikasi